RETURNING TO OFFLINE TEACHING AND LEARNING: WHAT IT MEANS FOR INDONESIAN STUDENTS AND TEACHERS - endang setyaningsih (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2022)
During the early pandemic, teachers and students were abruptly forced to conduct teaching and learning remotely. Both were struggling to cope with the challenges in the emergency remote teaching (ERT) situation. It was quite common to hear students and teachers wishing to go back to school immediately for various reasons. After two years of remote teaching, some schools begin to open for face-to-face or offline learning. It is then interesting to know how the students and teachers responded to the school/ campus opening. This paper reports a small-scale survey involving 110 respondents, both teachers, and students at the secondary and tertiary levels. Thematic coding analysis was carried out to analyze the participants’ responses. This study revealed that 80% of the respondents opted for online distance learning over offline learning during the pandemic although they reported challenges of teaching and learning within the online mode. The percentage shifted after two years of distance learning. In terms of mode preference, 56% of respondents prefer to go back to offline mode but the remaining 44% want to stay in the online remote mode of teaching and learning. While the majority chose offline learning, several themes of concern emerged from the responses, and reverse eco-shock is the most prominent. As the students and teachers acknowledged the benefits and build comfort in the online teaching and learning environment, they indicate the reimaging of offline teaching and learning. It implies that the practice of offline learning will not be similar to that before the pandemic